Survey on voters' attitudes and opinions regarding the role of the mass media during the 1990 Malaysian election campaign / Sankaran Ramanathan and Dr. Baharuddin Aziz - Ramanathan, Sankaran; Aziz, Baharuddin (Dr.) (Faculty of Communication and Media Studies (FCMS), 1994)
This survey of voters was conducted by a group of researchers from ITM in October 1990, beginning from the date of the nomination of candidates, starting from 6th October until 20th October, i.e, the election day. Each group was headed by a lecturer and assisted by 55 students who acted as research assistants.